(3ebOeI aj GdCYeGd hGdeGd (B/s - (3GdMfGhj, eMeO UGdMs; (3GdUMf, eMeO aQjO hBNQhfs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2000)
(3ebOeI Edi YGde GdCYeGd, eGgjI GdCYeGd, efXeGJ GdCYeGd, GdeTQhYGJ GdUZjQI, HjFI GdCYeGd, GJLGgGJ hJMOjGJ GdCYeGd aj GdCdajI GdKGdKI, hXGFa efXeGJ GdCYeGd, GSGSjGJ GdJShjb, GSGSjGJ GdGfJGL, CSGSjGJ GdehGQO GdHTQjI, GdGWGQ GdYGe dGOGQI GdGeOGO, GdTQGA hGdQbGHI Ydi GdeNRhf, GdeGd hGdCYeGd, CSGSjGJ GdJehjd, eUGOQ GdJehjd, eUGOQ GdJehjd bUjQI GdCLd, eUGOQ GdJehjd GdWhjd GdCLds
Keywords: (3EOGQI GdCYeGds; (3GdJehjds